Risque et vulnérabilité dans la recherche en santé urbaine - Brigit Obrist (VertigO)
Transformations in politics, environment and economy lead to rapid urbanization and increased risk and vulnerability for many population groups. Research on household economy identified three main features of urban vulnerability: commoditization, environmental hazards and social fragmentation. Various assets help people cope with their vulnerable condition. Building on this research we suggest an innovative approach combining the risk perspective of classic epidemiology with the vulnerability perspective of the social sciences. This approach informed a series of case studies in West Africa cities. They provide new insights into people’s exposure to health risk, their capacities and the level and type of potentiality within communities and households. We conclude that risk and vulnerability provide focal points for scientific assessment and political negotiation leading to locally appropriate and adapted public health actions.